Análisis clínico y microbiológico de la sepsis grave y el choque séptico por Escherichia coli en Medellín, Colombia (2019)
ABSTRACT: Background:Escherichia coli is a common cause of a broad spectrum of infections, from non-complicated urinary tract infection, to severe sepsis and septic shock, that are associated to high impact outcomes, such as ICU admission and mortality. Aims:To establish differences in mortality, ICU admission, ESBL positive strains and antibiotic treatment, between patients with E. coli related severe sepsis and septic shock, with or without bacteremia and its variability based on the source of infection. Method:Secondary data analysis of a multicentric prospective cohort study. Results:From 458 patients with E. coli isolation, 123 had E. coli exclusively in blood culture, 222 solely in urine culture, and 113 in both samples. Escherichia coli isolation exclusively in blood culture was associated with higher frequency of ICU admission (n = 63; 51.2%), higher rate of mechanical ventilation requirement (n = 19; 15.5%), higher mortality and longer hospital stay (n = 22; 18%; median of 12 days, IQR= 7 – 17, respectively); but with a lower occurrence of ESBL strains, compared to patients with positive urine culture and positive blood/urine cultures (n = 20; 17.7% and n = 46; 20.7%, respectively). 424 patients (92.6%) received antibiotic treatment in the first 24 hours. The most commonly prescribed was piperacillin/tazobactam (n = 256; 60.3%). The proportion of patients empirically treated with carbapenems vs non-carbapenems was similar in the three groups. Discussion:The source of infection, associated with ESBL strains risk factors, are useful tools to define prognosis and treatment in this population, because of their clinical and microbiological variability. Conclusion:Patients with E. coli isolation exclusively in the blood culture had higher frequency of non-favorable outcomes in comparison to patients with E. coli in urine culture with or without bacteremia. Additionally, in our population patients with E. coli solely in blood culture have lower prevalence of ESBL positive strains.